MODEL PENENTUAN STRATEGI PENGELOLAAN PERSEDIAAN BAHAN BAKU DENGAN METODE ANALYTICAL NETWORK PROCESS (ANP) (Studi Kasus di PT. LMM) - Sri Lestari (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
The success of raw material planning depends on the exact number of material of raw material needed; therefore the production will run properly. Base on this fact, the research conducted at PT Laser Metal Mandiri in PPIC department as the object this research focuses on how to overcome problem related to raw inventory, specifically making priority to strategy management raw material lack so that the production will keep running. In order to determine strategy management either tangiable or intangiable, Analytic Network Process (ANP) applied in this research that those analysis will show correlation among elements comprehensively. The criteria in this research comprise four aspects such as marketing or selling (C1), production (C2), purchasing (C3), and financing (C4), while the alternatives cover monthly demand (raw material) management (A1), maximum inventory level of raw material (A2), maximum-minimum production level (A3), and tracking management for certain sold product (A4). Based on the ANP method with software Super Decisions to A1 value of 0,095158, A2 value of 0,025463, A3 value of 0,026573, A4 value of 0,035432 dan A5 value of 0,064446.Keywords: Raw Material Planning, Strategy Management, Analytic Network Process (ANP), correlation, criteria